Evolutions of extracorporeal membrane oxygenator (ECMO): perspectives for advanced hollow fiber membrane - Fukuda, Makoto (Journal of artificial organs, 2024)
Hollow fiber membrane is incorporated into an extracorporeal membrane oxygenator (ECMO), and the function of the membrane determines the ECMO's functions, such as gas transfer rate, biocompatibility, and durability. In Japan, the membrane oxygenator to assist circulation and ventilation is approved for ECMO support. However, in all cases, the maximum use period has been only 6 h, and so-called ‘off-label use’ is common for ECMO support of severely ill COVID-19 patients. Under these circumstances, the HLS SET Advanced (Getinge Group Japan K.K.) was approved in 2020 for the first time in Japan as a membrane oxygenator with a two-week period of use. Following this membrane oxygenator, it is necessary to establish a domestic ECMO system that is approved for long-term use and suitable for supporting patients. Looking back on the evolution of ECMO so far, Japanese researchers and manufacturers have also contributed to the developments of ECMO globally. Currently, excellent membrane oxygenators and systems have been marketed by Japanese manufacturers and some of them are globally acclaimed, but in fact, most of the ECMO membranes are not made in Japan. Fortunately, Japan has led the world in the fields of membrane separation technology and hollow fiber membrane production. In the wake of this pandemic, from the perspective of medical and economic security, the practical use of purely domestic hollow fiber membranes and membrane oxygenators for long-term ECMO is imperative in anticipation of the next pandemic.